Microwave ablation vs. single-needle radiofrequency ablation for the treatment of HCC up to 4 cm: A randomized-controlled trial - Katsutoshi Sugimoto; Kento Imajo; Hidekatsu Kuroda; Go Murohisa; Kazue Shiozawa; Kentaro Sakamaki; Takuya Wada; Hirohito Takeuchi; Kei Endo; Tamami Abe; Takashi Matsui; Takahiro Murakami; et al. (JHEP Reports)
Background & Aims: Radiofrequency ablation (RFA) is the standard treatment for small hepatocellular carcinoma (HCC), specifically for tumors <3 cm in size and numbering fewer than three, excluding surgical candidates. Microwave ablation (MWA) is an innovative approach believed to have theoretical benefits over RFA; however, these advantages are yet to be empirically verified. Therefore, we evaluated and compared the effectiveness of MWA and RFA in managing HCC tumors up to 4 cm in size. Methods: In this multicenter randomized controlled trial conducted across five centers in Japan, eligible participants had up to 4 tumors, each up to 4 cm in size, and were not considered for surgery. Patients were randomly assigned to undergo MWA or RFA. The primary outcome was the rate of local tumor progression (LTP), whereas secondary outcomes included overall survival (OS) and intra- and extrahepatic recurrence-free survival (RFS) at the end of the 2-year follow up. Results: In total, 240 participants were screened from July 12, 2018, to December 7, 2021. Four participants were excluded: three did not meet inclusion criteria, and one died from an unknown cause during treatment. Consequently, 119 (130 lesions) and 117 (136 lesions) participants were treated with MWA and RFA, respectively. The proportion of lesions with LTP at the 2-year follow up was significantly lower in the MWA group (20 [16.4%] lesions) than in the RFA group (38 [30.4%] lesions) (risk ratio, 0.54; p = 0.007). OS and both intra- and extrahepatic RFS did not significantly differ between groups. Conclusions: MWA is more effective than RFA in reducing local tumor progression for HCC tumors up to 4 cm. However, no differences were observed in OS and RFS. Impact and implications:: While some randomized control trials (RCTs) have compared the efficacy of microwave ablation (MWA) and radiofrequency ablation (RFA) for small hepatocellular carcinoma (HCC), the superiority of MWA over RFA remains unverified despite its theoretical benefit. This study is the first to demonstrate the utility of MWA over single-needle RFA for patients with HCC, with a significant difference between the two groups in the proportion of lesions with local tumor progression after a 2-year follow up. Moreover, the two techniques were safe, with only two severe complications reported in the entire study cohort. Given that an RCT differs slightly from daily clinical situations, practical and anatomical criteria for selecting the optimal technique on a lesion-by-lesion basis are required.